HYPERLIPOPROTEINEMIAS - Нетюхайло, Л.Г. (World of Medicine and Biology, 2012)
In the article there are contemporary views about, based on data of literature of the native and foreign sources health beliefs type hyperlipoproteinemias.
Keywords: lipids; hyperlipoproteinemias